Meta-analysis of ATRIA versus CHA2DS2-VASc for predicting stroke and thromboembolism in patients with atrial fibrillation. (15th January 2017) - Zhu, Wengen; Fu, Linghua; Ding, Ying; Huang, Lin; Xu, Zhenyan; Hu, Jinzhu; Hong, Kui
Abstract: Background: Several studies have compared the discriminative performances of CHA2 DS2 -VASc and ATRIA scores, but the results are still disputed. Therefore, we aimed to explore their predictive abilities regarding stroke and thromboembolism (TE) risk in AF patients. Methods: We systematically searched the Cochrane Library, PubMed and ScienceDirect databases up to May 2016 for studies regarding CHA2 DS2 -VASc and ATRIA scores. The data were extracted and then pooled using Review Manager software version 5.30. Results: Six cohort studies with 363, 432 participants were included. Using the published cut-off points, the pooled C-statistics were 0.66 for ATRIA and 0.63 for CHA2 DS2 -VASc ( P diff  > 0.05). Using the optimized cut-off points, the C-statistics were 0.66 for ATRIA and 0.65 for CHA2 DS2 -VASc ( P diff  > 0.05). However, the ATRIA score presented a positive net reclassification improvement (NRI) value compared with the CHA2 DS2 -VASc score. In contrast, the CHA2 DS2 -VASc score classified fewer patients as low and moderate risk than the ATRIA score. The CHA2 DS2 -VASc score had lower event rates (either events per person or events per 100 person-years) in both the low and moderate risk categories compared with the ATRIA score. Conclusions: In combination with C-statistics and NRI values, the ATRIA score performed better than the CHA2 DS2 -VASc score for stroke risk prediction. In contrast, the CHA2 DS2 -VASc score was superior to the ATRIA score for identifying truly "low risk" AF patients. Highlights: ATRIA performed better than CHA2DS2-VASc for stroke risk prediction. CHA2DS2-VASc was superior to ATRIA for identifying truly "low risk" patients.